HERV‐K(HML‐2), a seemingly silent subtenant – but still waters run deep. Issue 1 (January 2016) - Hanke, Kirsten; Hohn, Oliver; Bannert, Norbert
Abstract : A large proportion of the human genome consists of endogenous retroviruses, some of which are well preserved, showing transcriptional activity, and expressing retroviral proteins. The HERV‐K(HML‐2) family represents the most intact members of these elements, with some having open and intact reading frames for viral proteins and the ability to form virus‐like particles. Although generally suppressed in most healthy tissues by a variety of epigenetic processes and antiviral mechanisms, there is evidence that some members of this family are (at least partly) still active – particularly in certain stem cells and various tumors. This raises the possibility of their involvement in tumor induction or in developmental processes. In recent years, many new insights into this fascinating field have been attained, and this review focuses on new discoveries about coevolutionary events and intracellular defense mechanisms against HERV‐K(HML‐2) activity. We also describe what might occur when these mechanisms fail or become modulated by viral proteins or other viruses and discuss the new vistas opened up by the reconstitution of ancestral viral proteins and even complete HML‐2 viruses.